Analysis of the Influence of Family Management, Family Ownership, Managerial Ownership, Institutional Ownership, Foreign Ownership and Family Involvement affect the Work Performance of Family Companies in Indonesia on the IDX - Tanita, Greceila Veronica; Yopie, Santi (Budapest International Research and Critics University, 2022)
Business or business is an effort to improve the economy of a country. This is because the income of a country is obtained from the income of taxes paid by business people in that country. Business is a business carried out by individuals, groups, organizations or even families who carry out an effort to generate added value for the business actors themselves. The research source data use historical data or research that uses external data archives of financial statements in the company's past (Indriantoro & Supomo, 2013). The coefficient of determination (adjusted R2) from the study is still minimal, namely 0.02% for ROA, 41.31% for ROE and 6.25% for Tobin's Q, which means the test variable cannot describe the dependent variable in this study.